Electrophysiological and Morphological Characterization of Neurons in the Granular Retrosplenial Cortex - (:unkn) unknown (My University, 2017)
The retrosplenial cortex (RSC) is a centrally located brain region that has reciprocal connections with several brain regions important for memory, including the prefrontal cortex, para-hippocampal region, hippocampal formation, and rhinal cortices. The RSC is also well connected with structures important for sensory processing, including the parietal cortex, thalamus, and visual cortices. Due to this connectivity, and early evidence that suggests the RSC plays a critical role in learning and memory, the region has recently gained much more research attention. Early studies found that patients with brain damage that includes the RSC have difficulty with verbal and visual information, retrieving recent autobiographical memories, and spatial navigation. Likewise, human research with neurologically intact participants suggests that the RSC could be involved in a wide range of cognitive processes, and early animal research supports this hypothesis as well. Specifically, rodent research on the RSC has demonstrated that the region supports tasks that involve spatial navigation, fear memory, and object recognition. For spatial tasks, the RSC seems to specifically be important for the use of distal cues to complete tasks like the radial arm maze, T-maze, and Morris water maze. For fear memory, the RSC is important for both trace and context fear memory, as well as extinguishing conditioned fear memory. Due to these findings, the RSC should be aggressively researched so that a complete understanding of the region and potential treatments for memory disorders and PTSD may be achieved in the near future. A large gap in our knowledge of the RSC is how the structure functions on the cellular level. In vivo electrophysiological studies, found that the RSC contains direction cells, and is active during the encoding of navigational cues, the encoding of a reward and its location, and during goal directed navigation. One study has examined the RSC at the single cell level, and reported regular-spiking and late-spiking neurons, but did not thoroughly characterize neurons in the RSC. Thus, the intrinsic electrophysiological and morphological properties of neurons in the RSC have not been thoroughly characterized. The present study sought to fill this gap in our knowledge of the RSC, and found four distinct populations of cells. Characterized by their firing patterns, neurons were classified as regular-spiking with a pronounced afterdepolarization (ADP-RS), double-spiking (DS), fast-spiking (FS), and late-spiking (LS) neurons. The current study examined intrinsic electrophysiological and morphological properties of these neurons and the underlying mechanisms mediating the afterdepolarization (ADP) and fast-spiking (FS) properties observed in granular retrosplenial cortical neurons. Using the synaptic blockers CNQX and D-AP5, we found that ionotropic glutamatergic synaptic input doesn’t significantly impact either of these properties. Using group 1 metabotropic glutamate receptor blockers LY367385 and MPEP we determined that the ADP property is at least partially mediated by these receptors. We used TEA to determine if the FS property is mediated by the voltage gated K+ channels Kv3.1-Kv3.2, and found that the FS property is likely partially mediated by these channels. These findings provide a foundation for understanding how the RSC may function to perform its important functions as well as shed light on how it may interact with other interconnected brain regions.
Keywords: Characterization; Electrophysiology; Morphology; Neurons; Retrosplenial Cortex